2015
DOI: 10.1002/app.43068
|View full text |Cite
|
Sign up to set email alerts
|

Performance and mechanism of laser transmission joining between glass fiber‐reinforced PA66 and PC

Abstract: On account of the large compatibility difference between glass fiber-reinforced Polyamide 66 (GFR-PA66) and Polycarbonate (PC), it is difficult to weld them directly by laser. A new technology is introduced in this article by which the transparent PC is successfully welded with GFR-PA66 using cold spraying in order to spray a 20 lm-thick aluminum film on GFR-PA66 as the absorbed layer. Tensile shear tests show the tensile strength of welded joints is highly enhanced. The influences of bubbles, glass fiber, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 20 publications
(22 reference statements)
0
4
0
Order By: Relevance
“…With rapid developments in automobiles, medical equipments, electrical appliances, and machinery industries, application scope of polyamides, owing to their excellent mechanical properties and high strength, has widely increased. [ 1–7 ] PA66 has excellent wear resistance, high mechanical strength, and heat resistance. However, PA66, an aliphatic polyamide, has glass transition temperature ( T g ) of only 70°C.…”
Section: Introductionmentioning
confidence: 99%
“…With rapid developments in automobiles, medical equipments, electrical appliances, and machinery industries, application scope of polyamides, owing to their excellent mechanical properties and high strength, has widely increased. [ 1–7 ] PA66 has excellent wear resistance, high mechanical strength, and heat resistance. However, PA66, an aliphatic polyamide, has glass transition temperature ( T g ) of only 70°C.…”
Section: Introductionmentioning
confidence: 99%
“…In 2015, Liu et al [ 8 ] successfully connected polyethylene (PE) and polyamide 66 (PA66) through the grafting modification of PE. In 2016, Liu et al [ 9 ] coated a thin layer of Al on the glass-fiber-reinforced PA66 surface by using cold spraying technology and successfully achieved the laser lap welding of PA66 and PC. Wang et al [ 10 ] enhanced the laser welding strength of polymethyl methacrylate (PMMA) and polybutylene terephthalate (PBT) by using PC film as the intermediate layer.…”
Section: Introductionmentioning
confidence: 99%
“…Other researchers have also shown that the surface free energy of materials is an important factor affecting the welding strength when they were studying laser transmission welding. For example, Liu et al investigated the laser transmission welding of PA66 with PVC [ 27 ]. It was found that the surface free energy of PA66 after surface magnetron sputtering of a layer of Al increased, so that PA66 and PVC, which could not be welded originally, were welded, forming a reliable connector through laser transmission welding by using Al atoms as a transition layer.…”
Section: Resultsmentioning
confidence: 99%